Blue LEDs: Pure Blue and Highly Luminescent Quantum‐Dot Light‐Emitting Diodes with Enhanced Electron Injection and Exciton Confinement via Partially Oxidized Aluminum Cathode (Advanced Optical Materials 11/2017). Issue 11 (June 2017) - Cheng, Tai; Wang, Zhibin; Jin, Shengli; Wang, Fuzhi; Bai, Yiming; Feng, Haoxian; You, Baogui; Li, Yang; Hayat, Tasawar; Tan, Zhan'ao
Abstract : High‐performance ZnCdS/ZnS graded core/shell blue quantum dot LEDs (QD‐LEDs) with a partially oxidized aluminum cathode (Al:Al2 O3 ) are demonstrated by Zhan'ao Tan and co‐workers in article number1700035 . Partial oxidation of the aluminum cathode is realized via simple autoxidation. In these blue QD‐LEDs, a record luminance of over 13 000 cd m −2 is achieved due to the dramatically enhanced electron injection from Al:Al2 O3 .